A note on the relationships between the stock market and macroeconomic variables in Malaysia: An empirical re-examination of Granger non-causality test - Habibullah, Muzafar Shah; Azali, M.; Azman-Saini, W.N.W.; Baharumshah, Ahmad Zubaidi (Universiti Utara Malaysia, 2000)
The purpose of the present paper is to determine whether stock returns are leading indicator for future economic activity in Malaysia. In this study we employ the Granger non-causality test recently proposed by Toda and Yamamoto (1995) to test the causal relationships between the KLSE stock prices and six macroeconomic variables for the sample period 1981:l to 1994:4. Our results indicate that stock prices are independent with respect with macroeconomic variables, except with money supply